2007
DOI: 10.1200/jco.2007.11.1765
|View full text |Cite
|
Sign up to set email alerts
|

Phase I and Pharmacokinetic Study of Lapatinib in Combination With Capecitabine in Patients With Advanced Solid Malignancies

Abstract: Lapatinib and capecitabine administered on a 3-week schedule were well tolerated, and no pharmacokinetic interaction was observed. Clinical activity was observed in patients with previously treated, advanced solid malignancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 17 publications
1
41
0
Order By: Relevance
“…A phase I pharmacokinetic study has shown that peak plasma concentration of lapatinib is 2.43 mg/mL (¼ 2.58 mmol/L; ref. 29). Consistently, lapatinib alone could not affect the viability of HER2-positive SCLC cells up to this concentration ( Supplementary Fig.…”
Section: Lapatinib Restores Chemosensitivity In Abc Transporter-positsupporting
confidence: 49%
“…A phase I pharmacokinetic study has shown that peak plasma concentration of lapatinib is 2.43 mg/mL (¼ 2.58 mmol/L; ref. 29). Consistently, lapatinib alone could not affect the viability of HER2-positive SCLC cells up to this concentration ( Supplementary Fig.…”
Section: Lapatinib Restores Chemosensitivity In Abc Transporter-positsupporting
confidence: 49%
“…Phase I clinical studies have proven the safety of lapatinib administration either alone 35,36 or in combination with another oral agent, capecitabine 37,38 . In the phase I study of Burris et al 36 , out of 67 patients with advanced solid tumors displaying HER1 expression by immunohistochemistry (IHC) and/or HER2 overexpression by IHC or amplification by fluorescence in situ hybridization (FISH) 30 (44.7%) were treated for BC.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…In the phase I study of Burris et al 36 , out of 67 patients with advanced solid tumors displaying HER1 expression by immunohistochemistry (IHC) and/or HER2 overexpression by IHC or amplification by fluorescence in situ hybridization (FISH) 30 (44.7%) were treated for BC. Patients who experienced complete remission, partial response (PR) or stable disease in the phase I studies were mainly those suffering from BC 36,38 . The phase II study in HER2+ MBC patients after trastuzumab treatment failure, produced more results supporting the safety of lapatinib and it evaluated its benefits 39,40 .…”
Section: Clinical Studiesmentioning
confidence: 99%
“…A phase I study (EGF10005) found the optimal tolerated regimen for the combination to be 1250 mg lapatinib daily and 2000 mg/m 2 /day capecitabine on days 1 to 14 of a 21-day cycle. Four confi rmed responses from 45 patients were reported, including 2 breast malignancies (1 complete response and 1 partial response) (Chu et al 2007). The complete response occurred in a patient that had disease progression while receiving trastuzumab.…”
Section: Lapatinib In Combination With Chemotherapymentioning
confidence: 99%
“…The AUC for SN-38 increased by 41% and C max increased by 32%. No significant pharmacokinetic interactions have been found between lapatinib and capecitabine (Chu et al 2007), trastuzumab , letrozole (GlaxoSmithKline), oxaliplatin and 5-FU (Siegel-Lakhai et al 2007), or docetaxel (GlaxoSmithKline).…”
Section: Potential Drug Interactionsmentioning
confidence: 99%